CMR nếu \(\frac{a}{b}=\frac{c}{d}\)thì \(\left(\frac{a-b}{c-d}\right)^4=\frac{a^4+b^4}{c^4+d^4}\)
CMR
Nếu \(\frac{a}{b}=\frac{c}{d}\) thì \(\left(\frac{a-b}{c-d}\right)^4=\frac{a^4+b^4}{c^4+d^4}\)
Ta có:
\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{a}{c}=\frac{b}{d}=\frac{a-b}{c-d}\Rightarrow\frac{a^4}{c^4}=\left(\frac{a-b}{c-d}\right)^4\left(1\right)\)
Từ \(\frac{a}{c}=\frac{b}{d}\Rightarrow\frac{a^4}{c^4}=\frac{b^4}{d^4}=\frac{a^4+b^4}{c^4+d^4}\left(2\right)\)
Từ ( 1 ) và ( 2 ) => \(\left(\frac{a-b}{c-d}\right)^4=\frac{a^4+b^4}{c^4+d^4}\)
\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{a^4}{b^4}=\frac{c^4}{d^4}=\frac{a^4-c^4}{b^4-d^4}=\left(\frac{a-c}{b-d}\right)^4\left(1\right)\)
\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{a^4}{b^4}=\frac{c^4}{d^4}=\frac{a^4+c^4}{b^4+d^4}\left(2\right)\)
từ (1) và (2) --> \(\left(\frac{a-c}{b-d}\right)^4=\frac{a^4+c^4}{b^4+d^4}\left(đpcm\right)\)
1) CMR: nếu \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}=\frac{d}{e}\) thì a\(\frac{a}{e}=\left(\frac{a-b+c-d}{b-c+d-e}\right)^4\)
b) \(2< \frac{\left(a+b\right)}{a+b+c}+\frac{\left(b+c\right)}{b+c+d}+\frac{\left(c+d\right)}{c+d+a}+\frac{\left(d+a\right)}{d+a+b}< 4\)
Cho a,b,c,d > 0 CMR :
a)\(A=\frac{\left(a+c\right)}{a+b}+\frac{\left(b+d\right)}{b+c}+\frac{\left(c+a\right)}{c+d}+\frac{\left(d+b\right)}{d+a}4\ge\)
b, \(\frac{a+b}{a+b+c}>\frac{a+b}{a+b+c+d}\); \(\frac{b+c}{b+c+a}>\frac{b+c}{a+b+c+d}\)
\(\frac{c+d}{c+d+a}>\frac{c+d}{a+b+c+d};\frac{d+a}{a+d+b}>\frac{a+d}{a+b+c+d}\)
Cộng các bĐT trên
=> \(B>\frac{2\left(a+b+c+d\right)}{a+b+c+d}=2\)
Ta có Với \(0< \frac{x}{y}< 1\)
=> \(\frac{x}{y}< \frac{x+z}{y+z}\)
Áp dụng ta có
\(B>\frac{a+b+d}{a+b+c+d}+...+\frac{d+a+c}{a+b+c+d}=3\)
Vậy 2<B<3
cho\(\frac{a}{b}=\frac{c}{d}\)CMR\(\frac{a^4+b^4}{c^4+d^4}=\left(\frac{a-b}{c-d}\right)^4\)
Ta có:\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{a}{c}=\frac{b}{d}\Rightarrow\frac{a^4}{c^4}=\frac{b^4}{d^4}=\frac{a^4+b^4}{c^4+d^4}\left(1\right)\)
Lại có: \(\frac{a}{c}=\frac{b}{d}=\frac{a-b}{c-d}\Rightarrow\frac{a^4}{c^4}=\frac{b^4}{d^4}=\left(\frac{a-b}{c-d}\right)^4\left(2\right)\)
Từ (1) và (2) => đpcm
CMR Nếu \(\frac{a}{b}=\frac{c}{d}\)thì:
a)\(\left(\frac{a-b}{c-d}\right)^4=\frac{a^4+b^4}{c^4+d^4}\)
b)\(\frac{5a+3b}{5a-3b}=\frac{5c+3d}{5c-3d}\)
c)\(\frac{7a^2+3ab}{11a^2-8b^2}=\frac{7c^2+3cd}{11c^2-8d^2}\)
b) Đặt \(\hept{\begin{cases}\frac{a}{b}=k\Rightarrow a=kb\\\frac{c}{d}=k\Rightarrow c=kd\end{cases}}\)
VT : \(\frac{5a+3b}{5a-3b}\Rightarrow\frac{5kb+3b}{5ka-3b}=\frac{b\left(5k+3\right)}{b\left(5k-3\right)}=\frac{5k+3}{5k-3}\) (1)
VP : \(\frac{5c+3d}{5c-3d}=\frac{5kd+3d}{5kd-3d}=\frac{d\left(5k+3\right)}{d\left(5k-3\right)}=\frac{5k+3}{5k-3}\) (2)
Từ (1) và (2) => đpcm
chứng minh rằng nếu\(\frac{a}{b}=\frac{c}{d}\)thì \(\frac{a^4+b^4}{^{c^4+d^4}}=\left(\frac{a-b}{c-d}\right)^4\)
cmr nếu \(\frac{a}{b}=\frac{b}{c}=\frac{c}{d}=\frac{d}{e}\)
thì \(\frac{a}{e}=\left(\frac{a-b+c-d}{b-c+d-e}\right)^4\)
Cho \(\frac{a}{b}=\frac{c}{d}\)
CMR : \(\frac{\left(a-b\right)^{\text{4}}}{\left(c-d\right)^4}=\frac{a^4+b^4}{c^4+d^4}\)a,b,c,d khác 0
Cho \(\frac{a}{b}\)= \(\frac{c}{d}\)CMR
a) \(\frac{a^2+b^2}{a^2+d^2}\)= \(\frac{\left(a+b\right)^2}{\left(c+d\right)^2}\)
b) \(\left(\frac{a-b}{c-d}\right)^4\)= \(\frac{a^4+b^4}{c^4+d^4}\)
a) Đặt \(\frac{a}{b}=\frac{c}{d}=k\Rightarrow a=bk;c=dk\)
Thay a = bk, c = dk vào \(\frac{a^2+b^2}{c^2+d^2}\) và \(\frac{\left(a+b\right)^2}{\left(c+d\right)^2}\), ta có:
\(\frac{\left(bk\right)^2+b^2}{\left(dk\right)^2+d^2}=\frac{b^2k^2+b^2}{d^2k^2+d^2}=\frac{b^2\left(k^2+1\right)}{d^2\left(k^2+1\right)}=\frac{b^2}{d^2}\)
\(\frac{\left(bk+b\right)^2}{\left(dk+d\right)^2}=\frac{\left[b\left(k+1\right)\right]^2}{\left[d\left(k+1\right)\right]^2}=\frac{b^2\left(k+1\right)^2}{d^2\left(k+1\right)^2}=\frac{b^2}{d^2}\)
Vì \(\frac{b^2}{d^2}=\frac{b^2}{d^2}\Rightarrow\frac{a^2+b^2}{c^2+d^2}=\frac{\left(a+b\right)^2}{\left(c+d\right)^2}\)
Vậy \(\frac{a^2+b^2}{c^2+d^2}=\frac{\left(a+b\right)^2}{\left(c+d\right)^2}\) với \(\frac{a}{b}=\frac{c}{d}\)
b) Thay a = bk, c = dk vào \(\left(\frac{a-b}{c-d}\right)^4\)và \(\frac{a^4+b^4}{c^4+d^4}\), ta có:
\(\left(\frac{bk-b}{dk-d}\right)^4=\frac{\left(bk-b\right)^4}{\left(dk-d\right)^4}=\frac{\left[b\left(k-1\right)\right]^4}{\left[d\left(k-1\right)\right]^4}=\frac{b^4\left(k-1\right)^4}{d^4\left(k-1\right)^4}=\frac{b^4}{d^4}\)
\(\frac{\left(bk\right)^4+b^4}{\left(dk\right)^4+d^4}=\frac{b^4k^4+b^4}{d^4k^4+d^4}=\frac{b^4\left(k^4+1\right)}{d^4\left(k^4+1\right)}=\frac{b^4}{d^4}\)
Vì \(\frac{b^4}{d^4}=\frac{b^4}{d^4}\Rightarrow\left(\frac{a-b}{c-d}\right)^4=\frac{a^4+b^4}{c^4+d^4}\)
Vậy \(\left(\frac{a-b}{c-d}\right)^4=\frac{a^4+b^4}{c^4+d^4}\) với \(\frac{a}{b}=\frac{c}{d}\)